From Concept to Clinic: The Expanding Frontier of Transethosome-Based Drug Delivery Systems - Salunke Harshada; Dr.Hangargekar Sachin; DongareDnyneshwar; Bamankar Akshay; Kharosekar Pooja (Asian Journal of Pharmaceutical Research and Development, 2025)
Transethosomes are an emerging class of ultra-deformable, lipid-based Nano carriers designed to overcome the limitations of conventional topical and transdermal drug delivery systems. As hybrid vesicles combining the characteristics of transferosomes and ethosomes, they incorporate phospholipids, ethanol, and edge activators to achieve exceptional flexibility, stability, and skin-penetration capability. This review highlights the fundamental principles, composition, and development of transethosomes, along with a detailed discussion of their various preparation techniques and evaluation parameters, including vesicle size, morphology, zeta potential, entrapment efficiency, elasticity, drug release behaviour, and stability. Their unique ability to enhance drug permeation through the stratum corneum enables the effective delivery of molecules ranging from small drugs to large biomacromolecules. Recent advancements demonstrate the broad therapeutic applicability of transethosomes in delivering antifungal, anti-inflammatory, anticancer, antibiotic, hormonal, ant arthritic, antihypertensive, ophthalmic, and cosmetic agents. With improved bioavailability, sustained release profiles, reduced systemic side effects, and high patient compliance, transethosomes represent a highly promising platform for innovative dermal and transdermal drug delivery.